(untitled) (REMUNOM, 2025)
This construct aims to review and analyze the main causes of the fall and low adherence to childhood immunization campaigns in recent years. Vaccination is a very efficient preventive practice against vaccine-preventable diseases and has ensured the eradication of several of them, reducing the high infant morbidity and mortality that plagued Brazilian public health. However, given the strengthening of anti-vaccination movements, the fragility of immunization campaigns, population unawareness regarding the severity represented by such diseases and several other behavioral postures, there is currently a worrying drop in childhood vaccination rates, raising the alert for the return of eradicated diseases. In this sense, this work is of fundamental relevance to the academic and scientific environment, as it contributes, through its content, to the discussions about the factors responsible for the current scenario in Brazilian immunology and, thus, boosting strategic planning works capable of bringing improvements in the immunization rates and vaccination coverage in the country.